Efeito da administração de cloridrato de fluoxetina em ratos submetidos a um modelo de parkinsonismo induzido por reserpina - Alvaia, Clarissa Gomes Andrade (2017)
Parkinson`s Disease is the second most common motor disorder and is also considered a progressive multisystemic disease associated to several nom motor symptoms (NMS), such as depression, with a prevalence of about 50% among PD patients. Selective serotonin reuptake inhibitors (SSIR) are the main treatment for this NMS, although researches with acutely induced parkinsonism has related fluoxetine to increased motor impairment. The aim of the present research is to evaluate the effect of the fluoxetine hydrochloride on a model of parkinsonism induced by low doses of reserpine. Sixty-four male 7-9-month-old Wistar rats were used, and were obtained from vivarium of the Department of Physiology – Federal University of Sergipe. Animals were divided into four groups: fluoxetine vehicle + reserpine vehicle (CTR); fluoxetine 10 mg/kg + reserpine vehicle (F); fluoxetine 10 mg/kg + reserpine 0,1 mg/kg (F + R); and fluoxetine vehicle + reserpine 0,1 mg/kg (R). During the treatment, the animals were submitted to open field test, catalepsy test and tremoulous jaw movement evaluation. It was shown that animals treated with fluoxetine and reserpine spent more time at the catalepsy test, decreased distance travelled, lower number of rearing at the open field test, increased tremulous jaw movements and increased weight loss. The treatment only with fluoxetine caused immunohistochemistry changes, such as decrease of TH expression in the dorsal striatum and increased staining of the dorsal raphe nucleus, with no correlation with MS for this group. The F + R group showed different immunohistochemistry results for both acute and continued administrations.